Stability of hold and postural control during static hold assessment can provide valuable information for biathlon standing shooting but aiming strategy should be acknowledged - Köykkä, M.; Laaksonen, M.; Ruotsalainen, K.; Linnamo, V. (European Journal of Sport Science, 2025)
This study investigated stability of hold and postural control in a static holding task and a biathlon standing shooting task, and shooting performance, examining the associations between these tasks and potential differences between biathletes employing a hold-based (HBS) or timing-based (TBS) aiming strategy. Twenty-two biathletes completed a static holding test in the standing shooting posture (Holding) and a biathlon standing shooting test (Shooting) using dry shots. Postural control was evaluated using force platforms, and stability of hold was assessed using a Vicon motion capture system (Holding) and a Noptel training device (Shooting). Of the stability of hold measures, links between the tasks were observed in aiming point vertical standard deviation (R = 0.78) and vertical mean velocity (R = 0.74) in HBS and in vertical mean velocity (R = 0.62) in TBS (all P < 0.05). Regardless of aiming strategy, most postural control measures in Holding correlated with their counterparts in Shooting (R = 0.48 to 0.94 and P < 0.05) and shooting performance (hit point distance from the centre of the target) correlated with stability of hold measured during Holding (R = 0.74 and P < 0.001). Among the postural control measures, shooting performance was only clearly linked to front leg postural control measured during Holding in TBS (R = 0.87 and P < 0.003). These findings suggest that static holding ability and postural control are important in biathlon standing shooting regardless of aiming strategy but aiming dynamics during Holding align more closely with the practices of HBS during their shooting.